Maturação fisiológica de sementes de Angico (Anadenanthera colubrina (Vellozo) Brenan) - Pires Neto, Paulo Affonso Fonseca [UNESP]; Pires, Victória Campos Monteiro [UNESP]; Moraes, Cristiano Bueno; de Oliveira, Lucicleia Mendes; Portella, Augustus Caeser Franke; Nakagawa, João [UNESP] (FapUNIFESP (SciELO), 2016)
The seed physiological maturity knowledgment is critical determine its maximum production and physiological quality. The objective of this study was to determine the ideal time to harvest by evaluating seeds physiological maturity. Seventeen weekly harvests of fruits and seeds from matrices located in the Brazilian city of Botucatu, SP, were performed from May to September 2001. Fruits size and weight, seed water content and dry matter, and germination and emission of primary root were evaluated. Seeds showed maximum dimension in the thirteenth week of collection, while the highest fruit weight was obtained in the twelfth week of collection. Water content decreased over time. Seeds dry matter showed its highest value in the sixteenth week harvest, while germination percentage showed its highest value between the fourteenth and fifteenth week harvest. The percentage of primary root emission was observed with maximum value in the tenth week harvest. Based on the results, it is concluded that the best Anadenanthera colubrina harvest season occurs between the fourteenth and fifteenth weeks.
Physiological ripening of Anadenanthera colubrina (Vellozo) Brenan seeds
Keywords: Forest seeds; Germination; Harvest period